NOMAC-E2 shows a better contraceptive effectiveness than LNG combined oral contraceptives in women under 25: real-world PRO-E2 study. (14th December 2023) - von Stockum, Sophia; Bauerfeind, Anja; Becker, Kerstin; Franke, Christian; Fruzzetti, Franca; Calaf, Joaquim; Keck, Christoph; Heinemann, Klaas
Abstract: Objective: To investigate unintended pregnancy and changes in mood, acne, and weight in NOMAC-E2 vs levonorgestrel-containing COC (COCLNG ) users under 25 years. Methods: In this large, observational study, new users (first-ever users of an eligible COC or restarting with the same or a new eligible COC after a break of at least 2 months) of NOMAC-E2 and COCLNG were recruited in 12 countries in Europe, Australia, and Latin America and followed up via questionnaires for up to 2 years. Unintended pregnancy was expressed by the Pearl Index (PI; contraceptive failures/100 women-years). Crude (HRcrude ) and adjusted hazard ratios (HRadj ) were calculated. Mood and acne changes were defined as change of score from baseline. Weight change was defined as percent change of body weight. Results: Overall, 12, 829 NOMAC-E2 users and 17, 095 COCLNG users under 25 were followed-up. The risk of unintended pregnancy was statistically significantly lower in the NOMAC-E2 cohort; confirmed events: 30 NOMAC-E2 (PI 0.24; 95% CI, 0.16–0.35) vs 94 COCLNG (PI 0.51; 95% CI, 0.41–0.62). The HRcrude for unintended pregnancy comparing NOMAC-E2 to COCLNG was 0.47 (95% CI, 0.31–0.71) and the HRadj was 0.52 (95% CI, 0.34–0.78). No differential effect on acne, mood, and weight was observed between cohorts. Conclusions: NOMAC-E2 shows a significantly better contraceptive effectiveness in young women and has no differential effect on acne, mood, and weight compared to COCLNG .